A organização social e o estabelecimento de redes sociais a partir do acesso às políticas públicas no Assentamento XX de Novembro, Cordeirópolis-SP - Filus, Veridiany (2017)
This dissertation brings a panorama of XX November Settlement, located in the municipality of Coordeirópolis-SP. It identifies its dwellers and expose informations as age, schooling, work/job and income; it maps the settlements that come under the scope of Pronaf, Pnae and PAA and analyses the networks built upon PAA and Pnae programs aiming to report the successes and hindrances for PAA and Pnae into the reality of the settlement and contribute to the improvement of the programs. In the first paper our first concern was analyzing the programs and policies towards familiar agriculture: PAA, Pnae and Pronaf in the context of XX November settlement. In order to do so, we've used the quantitative methodology as a tool, through the application of semi-structured questionnaires, as well as qualitative through the participative observation. In the second paper, we've analyzed how the relation between peasants from XX de Novembro Settlement and the organisms which represent them is configured. For such, we've used the systematization of questionnaires applied to the peasants along with the interviews with municipal agents and with the peasants representatives. Still, in the third paper, we analyze networks established around PAA and Pnae, in XX November Settlement, looking for understanding the impact of this network on the involved actors' social life. The informations were gathered by means of the instruments already mentioned while the overview on the first and second papers. Nevertheless, these informations were systematized with the help of the software Pajek prompting the network characterization and sociogram. In general we've identified that the community is composed by a equilibrated mix of men and women and that the community has an expressive number of its members with high school degree. Concerning to the acess to Pronaf, PAA and Pnae programs, Pronaf was the most accessed, from the beginning of the settlement up to 2016 nine families accessed PAA and two did access Pnae. The production outflowing to PAA and Pnae programs happens through the Cascalho Cooperative, Rio Claro Cooperative as well as directly to Rio Claro and Cordeirópolis municipalities and contributes for a R$ 1.086.47 monthly average income by family. Concerning to the attendings, in 2016 we've identified 5.118 attendings, by Pnae in Cordeirópolis, 39.000 by Pnae in Rio Claro and 850 baskets by PAA in Rio Claro, what adds up to an articulation of more than 48.000 people, only in this year. Meanwhile, concerning to social cohesion analysis, for this outflowing relation we've found a high degree of social cohesion improve the phrasing which reached to 85% what flags to a high integration between the outflowing net-work actors, being the issue on inspection, mainly of the amount of delivered food, the greatest difficulty pointed out within the net-work. Among the interviews' results, what has called our attention the most was peasants lack of information. Nevertheless this negative factor, regarding to the lack of information within the net, the issue on food quality improvement has been remarked, it was identified by the municipal agents who pointed out an improvement on the quality of the food received by schools and institutions and the educational factor added to the food being it purchased from the local familiar agriculture. With the aid of the software Pajek we achieved to identify some key relations and actors who will be able to play an outstanding role in order to enhance the programs from within; believing that keeping the focus on weak rings actors characterized so as having an intermediation role may be an strategy for relations improvement and widening within the net-work with no need to work review it throughly.